Effects of Simultaneous or Sequential Weight Loss Diet and Aerobic Interval Training on Metabolic Syndrome - Mora-Rodriguez, R.; Ortega, J. F.; Guio de Prada, V.; Fernández-Elías, V. E.; Hamouti, N.; Morales-Palomo, F.; Martinez-Vizcaino, V.; Nelson, R. K. (International Journal of Sports Medicine, 2016)
Our purpose in this study was to investigate efficient and sustainable combinations of exercise and diet-induced weight loss (DIET), in order to combat obesity in metabolic syndrome (MetS) patients. We examined the impact of aerobic interval training (AIT), followed by or concurrent to a DIET on MetS components. 36 MetS patients (54±9 years old; 33±4 BMI; 27 males and 9 females) underwent 16 weeks of AIT followed by another 16 weeks without exercise from the fall of 2013 to the spring of 2014. Participants were randomized to AIT without DIET (E CON, n=12), AIT followed by DIET (E-then-D, n=12) or AIT concurrent with DIET (E+D, n=12) groups. Body weight decreased below E CON similarly in the E-then-D and E+D groups (~5%). Training improved blood pressure and cardiorespiratory fitness (VO2peak) in all groups with no additional effect of concurrent weight loss. However, E+D improved insulin sensitivity (HOMA) and lowered plasma triglycerides and blood cholesterol below E CON and E-then-D (all P<0.05). Weight loss in E-then-D in the 16 weeks without exercise lowered HOMA to the E+D levels and maintained blood pressure at trained levels. Our data suggest that a new lifestyle combination consisting of aerobic interval training followed by weight loss diet is similar, or even more effective on improving metabolic syndrome factors than concurrent exercise plus diet.
Keywords: high intensity interval training; weight-reducing diet; metabolic syndrome; insulin resistance; maximal fat oxidation; DXA